The Association Between Social Media Use Intensity and Sleep Quality Among University Students at Universitas Graha Edukasi Makassar - Mustafa, Sri Resky; Toban, Rindani Claurita; Malfino, Yakobus Ning; Rajab, M. Alfian; Yunus, Suwardha; Mustafa, Saharuddin (Journal Kiara : Nursing and Midwifery, 2025)
Background: The development of digital technology and increased internet access have led to a significant rise in social media use among university students. Excessive intensity of social media use, especially at night, can affect sleep patterns and sleep quality. Insufficient sleep duration and poor sleep quality may have negative impacts on concentration, academic achievement, as well as students’ physical and mental health. Objective: To determine the relationship between the intensity of social media use and sleep quality among students at Universitas Graha Edukasi Makassar. Methods: This study employed a quantitative design with a cross-sectional approach. The research sample consisted of active students selected using purposive sampling techniques. Data were collected through a social media usage intensity questionnaire and the Pittsburgh Sleep Quality Index (PSQI) instrument to measure respondents’ sleep quality. Data analysis was conducted using univariate and bivariate methods with the chi-square test at a significance level of 0.05. Results: Most respondents had a high intensity of social media use and poor sleep quality. Bivariate analysis showed a significant relationship between the intensity of social media use and students’ sleep quality (p < 0.05). Students with high social media usage intensity tended to have poorer sleep quality compared to those with low to moderate levels of social media use.